Canada : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2003)
This Report on the Observance of Standards and Codes Data Module provides a review of Canada's data dissemination practices against the IMF's special data dissemination standard (SDDS), complemented by the in-depth assessment of the quality of six key sets of macroeconomic statistics: national accounts, consumer price index, producer price index, government finance statistics, balance of payments, and monetary statistics. Canada's macroeconomic statistics are of high quality. They are comprehensive, timely, and accurate, and thus are adequate to conduct effective surveillance of economic and financial policies.